Analisis Faktor Pencegahan Stunting di Kabupaten Muaro Jambi Tahun 2022 - Deasy Sumarni; Nur Alam Fajar; Hamzah Hasyim (Universitas Batanghari Jambi, 2022)
Stunting if the height of a child is not the same as the standard height of children in the normal population of the same age and sex. The National Medium-Term Plan (RPJMN) is to improve the nutritional status of the community, including reducing the prevalence of Stunting. This study aims to analyze in depth Human Development Cadre in preventing Stunting. Based on the results of the study by describing the phenomenon based on the perspective of the informants, finding various realities and developing a holistic understanding of a phenomenon in a particular context, it shows that the performance of the Human Development Cadre (KPM) in the Health Office of Muaro Jambi Regency depends on the involvement of cross-sectors in Stunting reduction acceleration program, in addition to cross-sectoral involvement, knowledge, the role of officers, training and support for government officials are very much needed to improve the performance of all Human Development Cadres (KPM) within the Muaro Jambi District Health Office. This research is a qualitative research by describing the phenomenon based on the point of view of the informants. The results of the performance of the Human Development Cadre (KPM) are still not in accordance with the guidelines, the role of officers in the KPM guide and the lack of knowledge of KPM in carrying out their duties.